2008
DOI: 10.18352/lq.7941
|View full text |Cite
|
Sign up to set email alerts
|

The Library as Strategic Investment: Results of the Illinois Return on Investment Study

Abstract: University administrators are asking library directors to demonstrate their library's value to the institution in easily articulated quantitative terms that focus on outputs rather than on traditionally reported input measures. This paper reports on a study undertaken at the University of Illinois at Urbana-Champaign that sought to measure the return on the university's investment in its library. The study sought to develop a quantitative measure that recognizes the library's value in supporting the university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…These articles contained many good ideas for aspects of library operations that can be measured, including indicators that are of interest to contemporary managers. Papers by Hershey, Kaufman, Aabo, ALIA, Bryant and Allen were assessed as informative but of variable quality and lacking in adequate supporting evidence. Gardois, Medernach, Marshall, Gray and Sievert provided evidence of the intangible benefits or the intrinsic value of clinical libraries but did not identify relevant values or costs of service delivery.…”
Section: Excluded Papersmentioning
confidence: 99%
“…These articles contained many good ideas for aspects of library operations that can be measured, including indicators that are of interest to contemporary managers. Papers by Hershey, Kaufman, Aabo, ALIA, Bryant and Allen were assessed as informative but of variable quality and lacking in adequate supporting evidence. Gardois, Medernach, Marshall, Gray and Sievert provided evidence of the intangible benefits or the intrinsic value of clinical libraries but did not identify relevant values or costs of service delivery.…”
Section: Excluded Papersmentioning
confidence: 99%
“…Previous studies have been conducted to answer questions such as "if one euro or more is invested, how many dollars or euros come back as income?" (Luther 2008) (Kaufman 2008). It has been more related to a perspective where income can take the shape of grants, for instance (Tenopir et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted at the University of Illinois at Urbana-Champaign determined a return of $4.38 in grant income to the university for every dollar invested in the library in 2006 (Luther, 2008;Kaufman, 2008). A subsequent study of nine universities showed variation in ROI based on grant money, ranging from 64 cents per dollar invested to $15 per dollar invested (Tenopir et al, 2010).…”
Section: Closing Argument and The Value Of Academic Librariesmentioning
confidence: 99%